Estimating the Impact of Postamputation Pain. Issue 5 (May 2022) - Liston, Jared M.; Forster, Grace L.; Samuel, Ankhita; Werner, Brian C.; Stranix, John T.; DeGeorge, Brent R.
Abstract : Supplemental digital content is available in the text. Abstract : Background: Neuromas, neuralgia, and phantom limb pain commonly occur after lower-extremity amputations; however, incidence of these issues is poorly reported and understood. Present literature is limited to small cohort studies of amputees, and the reported incidence of chronic pain after amputation ranges as widely as 0% to 80%. We sought to objectively investigate the incidence of postamputation pain and nerve-related complications after lower-extremity amputation. Methods: Patients who underwent lower-extremity amputation between 2007 and 2017 were identified using a national insurance-based claims database. Incidence of reporting of postoperative neuroma, neuralgia, and phantom limb pain were identified. Patient demographics and comorbidities were assessed. Average costs of treatment were determined in the year after lower-extremity amputation. Logistic regression analyses and resulting odds ratios were calculated to determine statistically significant increases in incidence of postamputation nerve-related pain complications in the setting of demographic factors and comorbidities. Results: There were 29, 507 lower amputations identified. Postoperative neuralgia occurred in 4.4% of all amputations, neuromas in 0.4%, and phantom limb pain in 10.9%. Nerve-related pain complications were most common in through knee amputations (20.3%) and below knee amputations (16.7%). Male sex, Charlson Comorbidity Index > 3, diabetes mellitus, diabetic neuropathy, diabetic angiopathy, diabetic retinopathy, obesity, peripheral vascular disease, and tobacco abuse were associated with statistically significant increases in incidence of 1-year nerve-related pain or phantom limb pain. Conclusions: Given the incidence of these complications after operative extremity amputations and associated increased treatment costs, future research regarding their pathophysiology, treatment, and prevention would be beneficial to both patients and providers.